Electron Beam-Induced Transformation in High-Density Amorphous Ices - Xu, Hongyi (J Phys Chem B, 2020)
[Image: see text] Amorphous ice is commonly used as a noncrystalline matrix for protecting sensitive biological samples in cryogenic electron microscopy (cryo-EM). The amorphization process of water is complex, and at least two amorphous states of different densities are known to exist, high- and low-density amorphous ices (HDA and LDA). These forms are considered to be the counterparts of two distinct liquid states, namely, high- and low-density liquid water. Herein, we investigate the HDA to LDA transition using electron diffraction and cryo-EM. The observed phase transition is induced by the impact of electrons, and we discuss two different mechanisms, namely, local heating and beam-induced motion of water molecules. The temperature increase is estimated by comparison with X-ray scattering experiments on identically prepared samples. Our results suggest that HDA, under the conditions used in our cryo-EM measurements, is locally heated above its glass-transition temperature.